Macular optical coherence tomography in patients with unilateral optic nerve hypoplasia - Abbasian, Javaneh (J AAPOS, 2015)
PURPOSE: To characterize the extent and location of macular thinning in patients with unilateral optic nerve hypoplasia (ONH) as compared to the contralateral normal eye. METHODS: The medical records of patients with unilateral ONH who underwent spectral domain optical coherence tomography (SD-OCT) of the macula were retrospectively reviewed. SD-OCT scans were manually segmented by 3 observers in 3 macular regions (superior, central, inferior). Boundaries identified included the inner limiting membrane, the junction between the inner nuclear layer and outer plexiform layer, and the neural retina–retinal pigment epithelium interface. Using custom MATLAB software, inner and outer retinal thickness profiles were quantified. A paired t test was used to compare the retinal thickness between the ONH eye and the contralateral normal eyes. RESULTS: Inner retinal thickness of the ONH eye was decreased in all areas of the macula (superior, central, and inferior) compared to the contralateral normal eye (P < 0.05). Outer retinal thicknesses were also decreased in the central and inferior sections compared with the normal eye (P < 0.05). CONCLUSIONS: Optic nerve hypoplasia is a congenital disease known to result in thinning of the nerve fiber and ganglion cell layer. Our small cohort demonstrated thinning of the inner retinal layers as well as the outer retinal layers in the ONH eye compared with the contralateral normal eye.